1993
DOI: 10.1073/pnas.90.11.5044
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the larval foraging gene affect adult locomotory behavior after feeding in Drosophila melanogaster.

Abstract: Previous (3); it is expressed only when food is present in the environment and when larvae are feeding (4).In the present paper, we examine adult fly walking behavior after feeding to determine whether the foraging locus affects adult behavior in a similar fashion to larval behavior. We found that adults homozygous for the forR allele walk farther from a drop of sucrose after feeding per unit time thanThe publication costs of this article were defrayed in part by page charge payment. This article must therefo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
151
3

Year Published

2000
2000
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(165 citation statements)
references
References 10 publications
11
151
3
Order By: Relevance
“…Larvae and adult flies with a rover allele (for R ) move greater distances while feeding than those with the sitter alleles (for s ) (Sokolowski, 1980;Pereira and Sokolowski, 1993). The for gene encodes a cGMP-dependent protein kinase (PKG) (Reaume and Sokolowski, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Larvae and adult flies with a rover allele (for R ) move greater distances while feeding than those with the sitter alleles (for s ) (Sokolowski, 1980;Pereira and Sokolowski, 1993). The for gene encodes a cGMP-dependent protein kinase (PKG) (Reaume and Sokolowski, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…PA and BUT were chosen, as they were unlikely to be odor equivalents; in larvae they are detected and processed by different combinations of peripheral and central structures (Kreher et al 2005). In addition, we found that larvae of the natural rover (for R ), sitter (for s ), and sitter mutant (for s2 ) strain, which was generated on a rover genetic background (de Belle et al 1989;Pereira and Sokolowski 1993), do not differ significantly in their response to these odors (below).…”
Section: Resultsmentioning
confidence: 95%
“…Natural strains of these larvae exhibit one of two foraging patterns: 'rover' larvae travel further than 'sitter' larvae in a single patch of food and move more between food patches [18,22]. In adulthood, the strains retain their separate foraging strategies [23], and rovers also acquire an enhanced sensitivity to sucrose [24]. Notably, rover and sitter locomotion activities do not differ significantly in the absence of food.…”
Section: Identification Of the Foraging Gene In D Melanogastermentioning
confidence: 95%